COMMERCIALISATION OF TRADITIONAL HERBAL PRODUCTS IN CENTRAL PROVINCE OF KENYA: CHALLENGES IN PROVIDING SUSTAINABLE SUPPLIES - Njoroge, Grace (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
In many African countries, medicinal bio-resources are seen as a vehicle to promote sustainable livelihoods of the communities through strategic and sustainable utilization. Globally, medicinal plants trade is estimated at US 800 million and is increasing at the rate of 7% per year. As the trade grows, species involved and their conservation status remain largely undocumented. An ethnobotanical study was undertaken in rural Central Province of Kenya determine important medicinal plants. Frequency of use among respondents and number of ailments each species manages were used as indices of importance. A market study was further undertaken to reveal critically important species for the trade as well as species in trade that are scarce. In total 89 species were identified as important in rural areas while only 8 species are most traded in urban centers. These results indicate that Aloe secundiflora, Senna didymobotrya and Vernonia lasiopus are not only the most frequently utilized but are also the ones managing most ailments and hence form the most significant medicinal plant species for the rural users. Most traded species include: Aloe secundiflora Engl, Urtica Massaica Mildbr, Prunus africana (Hook.f.) Kalkm, Melia volkensii and Strychnos henningsii. This study also reveals that Aloe secundiflora , Prunus Africana and Strychnos henningsii are the most needed in the market but in short supply. The supply chain in the rural and urban parts include plant species already known to be rare such as Carissa edulis and Synadenium compactum among others. Key words: medicinal plants trade, conservation, sustainable livelihoods.